Nonlinear Moderating Effect of Tenure on Organizational Identification (OID) and the Subsequent Role of OID in Fostering Readiness for Change. (February 2013) - Hameed, Imran; Roques, Olivier; Ali Arain, Ghulam
This empirical study investigates the curvilinear moderating effects of organizational tenure on the relationships between two status evaluations, that is, perceived external prestige (PEP) and perceived internal respect (PIR), and organizational identification (OID). This study validated the components of group engagement model in South Asian context, which highlighted the significant difference in the effects of status evaluations on OID. The importance of OID in the development of employee's readiness for change is also explored and tested. Survey method was used for collection of data from Pakistan. The results supported all the hypothesized relationships. This is one of the few studies which have explored the potential effects of organizational tenure on identification process, and tested the relationship between OID and readiness for change.